REVITALISASI NILAI-NILAI QUR’ANI DALAM PENDIDIKAN ISLAM ERA REVOLUSI INDUSTRI 4.0 - Siswanto Siswanto; Yuli Anisyah (Islamuna: Jurnal Studi Islam, 2018)
The existence of the 4.0 industrial revolution is seen as having a negative impact on the nation's morality. Given the latest western strategy in universalizing western civilization and its values. Through the Revolution 4.0 narrative wrapped in technological sophistication, it was intentionally designed for the acceleration of the industrialization of public demand so that the world depends on the west and there is hegemony in every aspect of life. Revitalizing the values of the Koran in the Islamic education system is a solution to maintain the swift flow of globalization and shifting values. If the Koran education continues to be developed, then the values of the Qur'an will become a spiritual capital to fortify itself from the impact of the 4.0 Industrial Revolution.[Keberadaan revolusi industri 4.0 dipandang akan memberikan dampak buruk bagi moralitas bangsa. Mengingat strategi terkini Barat dalam menguniversalkan peradaban Barat dan nilai-nilainya. Melalui narasi Revolusi 4.0 yang berbalut kecanggihan teknologi, sengaja dirancang bagi percepatan industrialisasi hajat publik agar dunia tergantung pada Barat dan terjadilah hegemoni dalam setiap aspek kehidupan.Revitalisasi nilai-nilai Alquran dalam sistem pendidikan Islam merupakan langkah solutif untuk mempertahankan derasnya arus globalisasi danpergeseran  nilai. Jika pendidikan Alquran terus dikembangkan, maka nilai-nilai Alquran akan menjadi modal spiritual untuk membentengi diri dari dampak Revolusi Industri 4.0 tersebut]